2023
DOI: 10.1007/s13167-023-00336-2
|View full text |Cite
|
Sign up to set email alerts
|

The correlation between primary open-angle glaucoma (POAG) and gut microbiota: a pilot study towards predictive, preventive, and personalized medicine

Abstract: Background Glaucoma is the leading cause of irreversible blindness worldwide. Emerged evidence has shown that glaucoma is considered an immune system related disorder. The gut is the largest immune organ in the human body and the gut microbiota (GM) plays an irreversible role in maintaining immune homeostasis. But, how the GM influences glaucoma remains unrevealed. This study aimed at investigating the key molecules/pathways mediating the GM and the glaucoma to provide new biomarkers for future p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“… 47 49 Chen et al identified NF-κB subunit 1 (NFKB1) as one of the hub genes in glaucoma that are gut microbiome-related. 50 These hub genes may affect glaucoma progression through several metabolites, including butyrate. Schulthess et al demonstrated that butyrate can imprint potent antimicrobial activity during macrophage differentiation.…”
Section: Discussionmentioning
confidence: 99%
“… 47 49 Chen et al identified NF-κB subunit 1 (NFKB1) as one of the hub genes in glaucoma that are gut microbiome-related. 50 These hub genes may affect glaucoma progression through several metabolites, including butyrate. Schulthess et al demonstrated that butyrate can imprint potent antimicrobial activity during macrophage differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Glaucoma, a prevalent and irreversible vision-impairing condition, is characterized by the gradual decline of retinal ganglion cells and their axons [ 1 , 2 ], resulting in narrowing of the visual field [ 3 ]. Over the past decade, there has been an increasing focus on exploring the connection between microbiota and glaucoma [ 5 , 6 , 42 , 43 ]. Microbiota imbalance (dysbiosis) triggered by various glaucoma risk factors, including aging [ 44 ], obesity [ 45 ], and depression [ 46 ], can lead to disruptions in metabolic, immune, and inflammatory processes.…”
Section: Discussionmentioning
confidence: 99%
“…Glaucoma can be divided into several subtypes, including primary open-angle glaucoma (POAG), primary angle-closure glaucoma (PACG), and secondary glaucoma. In POAG, serious damage may be caused to the optic nerve and the trabecular meshwork, which is the main pathway for drainage of aqueous humor and whose dysfunction leads to intraocular pressure (IOP) elevation [ 6 ]. The most common form of secondary glaucoma is pseudoexfoliation glaucoma (PEXG), caused by the deposition of fibrillar protein aggregates (PEX fibrils) on the anterior and posterior eye tissues [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, NLRP3 inflammasome activity was upregulated in the retina of glaucomatous DBA/2J mice [124]. TLR9 mRNA expression was significantly increased in trabecular meshwork from patients with POAG and in vitro TM culture systems [125]. In addition, cGAS-STING activity was increased in RGCs following ischemia/reperfusion and in poly(dA:dT)-treated BV-2 microglial cells [126].…”
Section: Role Of Aibp In Mitochondrial Dynamics and Function In Glauc...mentioning
confidence: 97%